A comparative study between the adsorption mechanisms of sodium co-silicate and conventional depressants for the reverse anionic hematite flotation. Issue 1 (2nd January 2022) - Tohry, A.; Dehghan, R.; Hatefi, P.; Chelgani, S. Chehreh
ABSTRACT: Starch, dextrin, sodium silicate (SS), and recently sodium co-silicate (SCS) are the most known depressants for the depression of iron oxides through the traditional reverse flotation. However, all these depressants' adsorption mechanisms on the surface of iron oxides and their main associated minerals (silicate and phosphates) through the reverse anionic flotation did not yet been thoroughly investigated. For filling this gap, as a comparative investigation, this study implemented Fourier Transform Infrared Spectroscopy (FTIR), zeta potential measurement, and micro-flotation tests to determine the adsorption mechanisms of these depressants and explored their effects on the floatabilities of pure hematite, quartz, and fluorapatite. Micro-flotation test results illustrated that all the examined depressants could depress hematite in the presence of an anionic collector. Still, the efficiencies of SS and SCS were higher than those of starch and dextrin. SCS had the lowest depression effect on quartz, and fluorapatite floatability compared to other depressants. Surface analyses depicted that dextrin and starch decreased the collector adsorption on the fluorapatite surface, where SCS and SS had a negligible effect on its floatability. The co-existence of physical and chemical bonds created between dextrin/starch and fluorapatite was the reason for its depression through the anionic reverse flotation.